Investigation of conventional and inverted organic solar cell from optical aspect. (2022) - Sen, Subhajit; Islam, Md. Rabiul
Abstract: As an interesting research topic, investigation on organic solar cells is increasing day by day. In this study, the performance of conventional P3HT: PCBM based organic solar cell (OSC) structure and inverted organic solar cell (IOSC) structure has been investigated through optical simulation using GPVDM software. As an active layer material, P3HT: PCBM is used. Al, ITO, PEDOT: PSS and T i O 2 is used as cathode, anode, hole transporting layer (HTL) and electron transporting layer (ETL) respectively for OSC structure. In case of IOSC, Ag has been used as an anode. Investigations have been made to study the effect of active layer thickness on the exciton generation rate. It has been found that the exciton generation rate is oscillatory due to optical interference effect for both OSC and IOSC structure. Photon absorption reduces due to increase in active layer thickness. However, exciton generation increases due to creation of more peak into the active layer.